If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3r + -1 = r + 1 Reorder the terms: -1 + 3r = r + 1 Reorder the terms: -1 + 3r = 1 + r Solving -1 + 3r = 1 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. -1 + 3r + -1r = 1 + r + -1r Combine like terms: 3r + -1r = 2r -1 + 2r = 1 + r + -1r Combine like terms: r + -1r = 0 -1 + 2r = 1 + 0 -1 + 2r = 1 Add '1' to each side of the equation. -1 + 1 + 2r = 1 + 1 Combine like terms: -1 + 1 = 0 0 + 2r = 1 + 1 2r = 1 + 1 Combine like terms: 1 + 1 = 2 2r = 2 Divide each side by '2'. r = 1 Simplifying r = 1
| 3ab-2bc=12c | | 5-10r+14= | | 30-4x=170-44x | | 3=(x+8)+14 | | 3n+15=6 | | -3g+6+g=15 | | 2n+-6=-8n+14 | | 2(n+.33)=1.5n+1+.5-.33 | | 3h+2=2h+7 | | 3x+3-6x=36 | | 50=2l+2(15) | | -6(16)= | | 4(8+-5u)=-2u-4 | | 4k+mn=n-3n | | 8(2w-6)+4(-1-5w)=-8 | | 2-3x=3x-4 | | 8=(3m+4) | | 12.06m-4.4-4.8m=2.4 | | 2w-1=w | | x^3=210 | | 7X=3Y+6-5X | | 9+6x=75 | | 2x-8=1x-24 | | (x+1)(x-1)=o | | 3(2x-4)-4=4x+1 | | -2c-1=-c-4 | | 6=(2m+7) | | 4k-2=2k+4 | | 240.00+x(0.25)=405.00 | | 2(0.3x+4)-1=1.33x-3+x | | 25+(5x)=50+(10x) | | 10pq+8p= |